2.5D geophysical model of the Gällivare mining area: An integrated study to model the top 4 km of the subsurface and guide for future exploration activities. (8th March 2021) - Tavakoli, Saman; Sarlus, Zmar; Kronsell, Ida; Bauer, Tobias E.
ABSTRACT: Potential field and Slingram data alongside rock physical properties, drill‐core information and results from geological field mapping were used to investigate the geometry of the geological structures in the Gällivare area in regional scale. The main purpose of this study was to delineate the vertical and lateral extension of the Malmberget felsic volcanic rocks, the Dundret and Vassaravaara units as well as geological structures related to the crustal‐scale Nautanen deformation zone. Furthermore, we aimed at identifying new magnetite‐hematite and sulphide mineralizations and lithologies related to the mineralizations based on the results from regional‐scale potential field modelling which are delineated with rock physical properties and borehole data. The study result indicated that the dome‐shaped Dundret gabbro extends downwards to ∼4 km depth and has its maximum depth at its centre. Hematite and magnetite assemblages occur within the top 2 km of the Dundret complex. Felsic volcanic rocks in the Malmberget area extend vertically down to a maximum depth of ∼3 km and get considerably thinner towards the west. The model for the known magnetite‐rich mineralizations in Malmberget was inferred from earlier drilling activities and was integrated into the profile models, which indicates a reasonable fit to the measured data, in particular on the magnetic anomaly; whereas the small dimensions of the modelled structures make them invisible on the Bouguer anomaly data. Additional magnetite‐rich mineralizations are suggested within the Malmberget felsic rocks. High real component and low imaginary response of the Slingram data suggests conductive zones within the Nautanen deformation zone towards the NE, which given the geology of the area in the high strain zone can indicate disseminated sulphide mineralizations. Drill‐hole data at the eastern parts of W‐E profiles agreed well with the suggested model inferred from potential field data, suggesting presence of mafic intrusions within the ∼top 1 km of the subsurface. The integrated model based on geophysical, petrophysical and geological data improved earlier understanding about the regional geometry of the key structures in the Gällivare area and indicates new magnetite‐rich and sulphide mineralization prospects which can be used as a guide for future exploration activities in the area.